KEDUDUKAN WANITA DALAM HUKUM NEGARA DAN HUKUM ISLAM DI REPUBLIK INDONESIA DITINJAU DARI HUKUM INTERNASIONAL - Mas’ud, Muhamad; Rahmawati, Aslihatul (An Nawawi, 2024)
With Law Number 7 of 1984 (Law No.7/1984), the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) was ratified. According to the rules of international law known as pacta sunt servanda, international agreements that have been ratified must be implemented. Countries in the world may not be exempted from this obligation based on the provisions of their national laws. However, if national law reduces the implementation of an international agreement, the national law must be changed. This obligation is added to the CEDAW article which states that CEDAW Parties are required to change national laws to eliminate discrimination against women and protect women's rights. However, in Indonesia, the elimination of discrimination against women and the protection of women's rights as well as changes to the law are more complicated than the words of the rules of international law. The implementation of CEDAW contains problems in the political field, especially after the replacement of the New Order government with the Reformation Era government. Political problems are added to social problems, namely developments and differences of opinion in society regarding culture and religion. In the state legal system, the examination of these issues shows that the recognition of the principle of eliminating discrimination against women and equal rights for women is good. This recognition is contained in the 1945 Constitution and Pancasila which can be improved along with the Decree (TAP) of the People's Consultative Assembly (MPR) Number XVII/MPR/1998 concerning Human Rights (HAM) and Law No. 39/1999 concerning Human Rights which are complete. In Indonesia, the enforcement of these laws and regulations needs to be improved. This enforcement includes, among other things, the authority to test in the general court environment and the state administrative court (TUN). The scope of the existing authority to test means that the majority of laws and regulations (including TUN Decisions) cannot be tested against the principle of discrimination or women's rights. So, the majority of laws and regulations may be issued and apply whether they are discriminatory and violate women's rights or not. With this examination, this paper concludes that the position of women in Indonesia as outlined by CEDAW needs to be realized through legal changes both in the state legal system and the Islamic legal system. However, this paper acknowledges the differences between the Islamic legal perspective and the CEDAW perspective. The ambiguity of the relationship between Islamic law and CEDAW is a product of the difficulty of harmonizing these angles.